Social Communication of Maternal Immune Activation-Affected Offspring Is Improved by Si-Based Hydrogen-Producing Agent - Usui, Noriyoshi; Matsumoto-Miyai, Kazumasa; Koyama, Yoshihisa; Kobayashi, Yuki; Nakamura, Yukiko; Kobayashi, Hikaru; Shimada, Shoichi (Frontiers in Psychiatry, 2022)
Maternal immune activation (MIA) is triggered by infection or autoimmune predisposition during pregnancy, and cytokines produced by MIA are transmitted through the placenta to the fetal brain, implicating in the onset risks and vulnerability for the developmental and psychiatric disorders such as autism spectrum disorder (ASD) and schizophrenia. To address these kinds of problem in the child health, we have developed a silicon (Si)-based hydrogen-producing antioxidant (Si-based agent) that continuously and effectively produces hydrogen in the body. Medical hydrogen is known to have antioxidative, anti-inflammatory, and antiapoptotic effects, therefore we applied our Si-based agent as a potential therapeutic agent to MIA. Using a MIA mouse model, we found that Si-based agent improved social communication of MIA offspring mice. We also found that the Si-based agent suppressed the expressions of inflammation associated genes Ifna1 and Il-6 in the mouse brain. These results demonstrate that Si-based agent is an effective prophylactic agent against MIA during pregnancy, suggesting that our Si-based agent may be a preventative or therapeutic agent for ASD and other disease risks in the child health by suppressing MIA damage.